MENGUKUR TINGKAT PEMAHAMAN SISWA TENTANG METAMORFOSIS MELALUI MEDIA GAMBAR DAN VIDEO ANIMASI DIKELAS III MI AL HUSNA - Atikah Lutfi Kinanti; Al Amin (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
This study aims to optimise pupils’ understanding of metamorphosis through the use of images and animated videos among Year 3 pupils at MI Al Husna. The background to this study is based on pupils’ low understanding of the process of change in living organisms, due to teaching methods that remain conventional and unengaging. The study employed a Classroom Action Research (CAR) approach, conducted over two cycles. The subjects of the study were 24 third-year pupils at MI Al Husna. Data collection techniques included observation, learning outcome tests and documentation. The results of the study indicate that the use of images and animated videos can optimise pupils’ understanding of metamorphosis. This is evident from the improvement in pupils’ learning outcomes in each cycle. In the pre-action phase, the average student score was 62 with a mastery rate of 45%. Following the implementation of the media in Cycle I, the average score rose to 74 with a mastery rate of 71%. In Cycle II, the average student score increased further to 86 with a mastery rate of 92%. The use of images and animated videos not only contributes to optimising students’ learning outcomes but also encourages their more active participation during the learning process, making students more enthusiastic and better able to understand the stages of metamorphosis in a tangible way. Images and animated videos can be implemented as an effective alternative teaching method to support the improvement of primary school students’ understanding of science.